TEACHING AND LEARNING OF ORGANIC CHEMISTRY BASED ON BLOOM'S TAXONOMY (19 - 37) - Mohd Jais, Samsiah; Mohammad, Nurul Hidayu; Mohammad, Aisyah; Bistamam, Mohd Nasir (Jurnal Pendidikan Bitara UPSI, 2019)
This paper reports a qualitative study based on document analysis to characterize the teaching and learning of Matriculation Organic Chemistry, Ministry of Education based on revised Bloom's Taxonomy. Document analysis was conducted on three elements: a description of the syllabus, questions of tutorials exercise and final examination questions. From the analysis of documents based on Bloom's Taxonomy, it is found that the three elements are concentrated at low cognitive level. This study also identified a significant gap between the three objectives of the course; enable students to master the basic concepts of chemistry; develop science and problem-solving skills; allows students to use their knowledge and skills in new situations and daily life, with what is shown by the documents analyzed. This paper also proposes an explanation that this gap is due to the traditional view of education that fails to see the chemistry education as a whole framework and steps to improve the teaching and learning of the topics studied.